Post infectious IBS: defining its clinical features and prognosis using an internet-based survey - Card, Timothy; Enck, Paul; Barbara, Giovanni; Boeckxstaens, Guy E.E; Santos, Javier; Azpiroz, Fernando; Mearin, Fermin; Aziz, Qasim; Marshall, John; Spiller, Robin C. (SAGE, 2018)
Background: Gastrointestinal infection is an important risk factor for developing IBS. Our aim was to characterise postinfectious IBS (PI-IBS) compared to other IBS patients. Methods: An internet survey of IBS patients using Rome III diagnostic questionnaire, Hospital Anxiety & Depression Scale (HADS) and Patient Health Questionnaire-12 somatic symptom score (PHQ12-SS) documenting the mode of onset. Results: 7811 participants, 63.2% female of whom 1004 (13.3%) met criteria for PI-IBS. 70% of PI-IBS described sudden onset, 35% onset while travelling, 49.6% vomiting, 49.9 fever and 20.3% bloody diarrhoea. Compared to other IBS, PI-IBS was significantly associated with living in Northern Europe and North America, having a hysterectomy, not having an appendectomy, higher PHQ12-SS score and having more than one toilet in the family home. PI-IBS patients had more frequent stools. At 1 year recovery rate in PI-IBS and non-PI-IBS group was 19.7% and 22.2%, p=0.15. Recovery rates were lower for females (20.7%) versus males (38.8%), those with somatisation ( 23.0%) versus those without (33.2%) and living in North America or Northern Europe (21.1%) versus living elsewhere (33.9%) p=<0.001. Conclusion: PI-IBS accounts for around 13% of all IBS in this internet sample, with some distinctive features but a similar prognosis to the remainder.